2022
DOI: 10.3390/biom12121782
|View full text |Cite
|
Sign up to set email alerts
|

Hub Genes in Non-Small Cell Lung Cancer Regulatory Networks

Abstract: There are currently no accurate biomarkers for optimal treatment selection in early-stage non-small cell lung cancer (NSCLC). Novel therapeutic targets are needed to improve NSCLC survival outcomes. This study systematically evaluated the association between genome-scale regulatory network centralities and NSCLC tumorigenesis, proliferation, and survival in early-stage NSCLC patients. Boolean implication networks were used to construct multimodal networks using patient DNA copy number variation, mRNA, and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…Through the enriched function analysis, we found that CLEC4M may play an important role in the activation and response of immune cells, comprising T cells, lymphocytes, myeloid leucocytes, macrophages, further confirming the crucial role of CLEC4M in immune activity, and uncovered the potential mechanism by which CLEC4M affected NSCLC microenvironment. Recently, Ye et al 49 integrated CNV-mediated transcriptional networks, mRNA co-expression, and protein co-expression networks to reveal associations between multi-omics network centrality and NSCLC oncogenesis, proliferation, and patient survival, demonstrating the immunotherapy targets including PD1, PDL1, CTLA4 and CD27, were the top hub genes in most of the constructed multi-omics networks in NSCLC tumors. In Yu’s study, 50 SPP1 was identified as a biomarker of NSCLC, which has significant coexpression relation to PD1 and PDL1, and acted as an immune-related target.…”
Section: Discussionmentioning
confidence: 99%
“…Through the enriched function analysis, we found that CLEC4M may play an important role in the activation and response of immune cells, comprising T cells, lymphocytes, myeloid leucocytes, macrophages, further confirming the crucial role of CLEC4M in immune activity, and uncovered the potential mechanism by which CLEC4M affected NSCLC microenvironment. Recently, Ye et al 49 integrated CNV-mediated transcriptional networks, mRNA co-expression, and protein co-expression networks to reveal associations between multi-omics network centrality and NSCLC oncogenesis, proliferation, and patient survival, demonstrating the immunotherapy targets including PD1, PDL1, CTLA4 and CD27, were the top hub genes in most of the constructed multi-omics networks in NSCLC tumors. In Yu’s study, 50 SPP1 was identified as a biomarker of NSCLC, which has significant coexpression relation to PD1 and PDL1, and acted as an immune-related target.…”
Section: Discussionmentioning
confidence: 99%